Effects of mouth rehabilitation with removable complete dentures on stimulus perception and the electromyographic activity of the orbicularis oris muscle - Caxias, Fernanda P. de [UNESP]; Santos, Daniela M. dos [UNESP]; Goiato, Marcelo C. [UNESP]; Bitencourt, Sandro B. [UNESP]; Silva, Emily V. F. da [UNESP]; Laurindo-Junior, Murilo C. B. [UNESP]; Turcio, Karina H. L. [UNESP] (Elsevier B.V., 2018)
Statement of problem. Many elderly individuals are rehabilitated with removable complete dentures, which require an initial adaptation period for both oral perception and the perioral muscles. Studies assessing the changes in stimulus perception and the electromyographic (EMG) activity of the orbicularis oris muscle shortly after conventional complete denture insertion are lacking. Purpose. The purpose of this clinical study was to evaluate the effect of mouth rehabilitation with removable complete dentures on stimulus perception and the EMG activity of the orbicularis oris muscle. Material and methods. This study was approved by the Human Research Ethics Committee of the Aracatuba Dental School (Sao Paulo State University). Fifteen participants who had worn their removable complete dentures for at least 5 years and needed rehabilitation with new prostheses were enrolled in the study. A perception questionnaire was applied, and surface EMG examinations of the orbicularis oris muscle during rest, suction of water with a straw, and pronunciation of the syllables /bah/, /mah/, /pah/, and the word 'Mississippi' were performed before (TO) and 30 (T1) and 100 (T2) days after insertion of the new prostheses. The data were analyzed with the Cochran Q test, McNemar test, 2-way repeated measures ANOVA, and honestly significant difference (HSD) Tukey test (alpha=.05). Results. Significant improvement was reported in the perception questionnaire in terms of the oral discomfort sensation in the T2 period. EMG activity decreased during rest and suction after insertion of the new prostheses. A statistical difference between the upper and lower fascicles of the orbicularis oris muscle was detected, with a decrease of EMG activity between the T0 and T1 periods on the lower fascicle, except for when pronouncing the /pah/ syllable. Conclusions. Mouth rehabilitation with removable complete dentures decreased oral discomfort and, depending on the oral function, decreased or increased EMG activity of the orbicularis oris muscle. In addition, the lower fascicle was more active than the upper fascicle during rest and most functional activities.